PENGARUH SHARIAH GOVERNANCE DAN ISLAMIC SOCIAL REPORTING TERHADAP KUALITAS TATA KELOLA PERBANKAN SYARIAH - Andika Rendra Bimantara; I Gusti Ayu Agung Omika Dewi (Universitas Pendidikan Nasional, 2019)
The Infuence of Shariah Governance and Islamic Social Reporting on the Quality of Syariah Banking Governance.This study aims to determine whether shariah governance and islamic social reporting affect the quality of islamic banking governance in Indonesia. Data were collected using documentation method. The population used in this study was all Islamic banking listed in the Directory of Bank Indonesia. Purposive sampling method was applied to determine the sample. The analytical method used is quantitative analysis, namely multiple linear regression analysis using SPSS test. The results of the F test show that shariah governance and islamic social reporting influence the quality of islamic banking governance. While the results of the t test show that 1) shariah governance influences the quality of sharia banking governance 2) islamic social reporting influences the quality of sharia banking governance. The coefficient of determination () is 0.672, which means that the influence of the independent variables on the dependent variable is 67.2%. Whereas 32.8% is explained by other factors not tested in this study.Keywords: shariah governance, islamic social reporting, quality of islamic banking governance, self assessment